Integrated electronic nose and multi-omics reveal changes in flavour characterization of cashmere goats and tan sheep meat - Ju Zhang; Shuang Pang; Ge Yan; Lulu Wang; Yuan Xu; Yuheng Bai; Ran Li; Xihong Wang; Yu Jiang (Food Chemistry: X)
This study aimed to employ a multi-omics method to identify key compounds contributing to the sensory flavour of mutton and to investigate the internal correlation between volatile metabolites and lipids in Cashmere goats and Tan sheep. The results demonstrate that the electronic nose can effectively and quickly distinguish goats and sheep meat. A total of 18 volatile metabolites and 314 lipids were identified as significant contributors to the flavour difference between goats and sheep meat, as determined by HS-SPME-GC–MS and lipidomic respectively. Specifically, TG(18:1/20:4/20:4), TG(18:1/18:2/20:4), TG(18:1/18:1/20:4), DG(18:0/20:4), and dodecanoic acid influence flavour by participating in key KEGG pathways such as the “fat digestion and absorption”, “cholesterol metabolism” and “lipid and atherosclerosis”. This study lays the groundwork for understanding the sources and mechanisms of mutton flavour compounds, providing valuable insights to support the growth and development of the mutton industry.